Depositional Environment Analysis of Kais Formation in Identification Reservoir Potential on Sowai Exploration Field, Bintuni Basin, West Papua - DONURIZKI (NIM : 12011031), AGUNG
As an exploration field, Sowai field is located in Bintuni basin, Bird's Head Papua Region, West Papua which has area around 250 km2. Research is conducted on Miocene Kais Formation in Sowai field. The aims of this study is to determine sedimentation process, depositional environment, and depositional facies of Kais Formation in the research field and surround it, determine structure that affected Kais Formation, determine distribution of Kais Formation in the research field, and identify Kais Formation potential as a reservoir in this field. Based on cutting, biostratigrafi, and literature analysis, Kais Formation is deposited in Early-Middle Miocene. The Kais Formation mapping resulted that there is a partial erosion until total erosion in the SW part of the research field. The Kais Formation in the research area and surrounding area have five seismic facies, there are seismic facies 1 as platform interior, seismic facies 2 as platform margin/ shelfedge, seismic facies 3 as slope, seismic facies 4 as deeper marine, and seismic facies 5 as channel. Seismic facies 5 is a channel geometry which is formed by incision mechanism from the erosion of Kemum High when the sea level drop. That channel can be used as a permeability barrier of stratigraphic trap in the Kais Formation reservoir. The dominant structure in the research area has NW-SE orientation. Geological subsurface analysis of Kais Formation come in a few potential as 4 way dip structural trap and 3 way dip against channel (combination trap). Volumetric calculations is used to predict the hydrocarbon volume in the reservoir (with trap). Using the assumption that hydrocarbon in the trap is oil based on data that there is a good oil show in Dowai-1 well, the biggest volume that is resulted from the calculations is around 24,042,878.05 STB.